2015
DOI: 10.1083/jcb.201404095
|View full text |Cite
|
Sign up to set email alerts
|

The Nck-interacting kinase NIK increases Arp2/3 complex activity by phosphorylating the Arp2 subunit

Abstract: Arp2 phosphorylation by the kinase NIK increases the actin-nucleating activity of the Arp2/3 complex and is necessary for plasma membrane protrusion in response to EGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 36 publications
5
42
1
Order By: Relevance
“…MAP4K4 modulates the remodeling of the F-actin cytoskeleton in response to growth factors (GF) such as HGF, EGF and PDGF or the pro-inflammatory cytokine TNFα, both by directly controlling polymerization dynamics as well as signaling mediators associated with cytoskeleton control. The tripartite mechanism control of F-actin remodeling by MAP4K4 through pH regulation [13], actin polymerization and branching [15] and F-actin anchoring [14], strongly argues for MAP4K4 effectively translating growth factor (GF) signaling into cytoskeleton alterations affecting not only the overall morphology of the cell, but also how signals are transmitted inside the cell and how surface receptors are made available. Such alterations also support the disease conditions MAP4K4 was found associated with, in particular in pathological angiogenesis and cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAP4K4 modulates the remodeling of the F-actin cytoskeleton in response to growth factors (GF) such as HGF, EGF and PDGF or the pro-inflammatory cytokine TNFα, both by directly controlling polymerization dynamics as well as signaling mediators associated with cytoskeleton control. The tripartite mechanism control of F-actin remodeling by MAP4K4 through pH regulation [13], actin polymerization and branching [15] and F-actin anchoring [14], strongly argues for MAP4K4 effectively translating growth factor (GF) signaling into cytoskeleton alterations affecting not only the overall morphology of the cell, but also how signals are transmitted inside the cell and how surface receptors are made available. Such alterations also support the disease conditions MAP4K4 was found associated with, in particular in pathological angiogenesis and cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the TNFα-receptor, growth factors (GF) such as PDGF or EGF activate MAP4K4 through receptor tyrosine kinases (RTKs) [2] and trigger the phosphorylation and activation of the MAP4K4 substrates sodiumproton exchanger [1] (NHE1) [13], ezrin, radixin, moesin (ERM) family proteins [14] and actin-related protein [2] (Arp2) [15]. Genetic studies in C. elegans identified an interaction between the worm ortholog of MAP4K4-MIG-15-and integrin/PAT3 [16].…”
Section: Signaling Through Map4k4mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a comprehensive set of direct Map4k4 substrates is not yet available, several studies have identified Map4k4 as an upstream regulator of proteins involved in cytoskeletal dynamics or adhesion including Arp2 [49], Farp1 [50], moesin [39], IQSEC [51] and Pyk2 [10]. Deletion of Map4k4 in endothelial cells altered membrane dynamics resulting in reduced endothelial cell migration and impaired angiogenesis [39].…”
Section: Signaling Pathways Of Map4k4: Activators and Effectorsmentioning
confidence: 99%
“…Among the remaining challenges is systematic identification of upstream activators as well as effectors of Map4k4 function (see Outstanding Questions). Several substrates of Map4k4 have been reported [39, 49, 50, 53, 54] and phosphopeptides dependent on Map4k4 activity identified in HepG2 cells [50] but further identification and validation of Map4k4 targets in tissues of interest should be informative.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%